Is AI Cost-Effective for Rare Disease Diagnosis? A Deep Dive into Digital Health Economics - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The journey to a rare disease diagnosis is often described as an "odyssey"—a long, arduous, and costly endeavor. With over 7,000 identified rare diseases, co...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine